Structural Equation Model Evaluating Katz's Triplet Managerial Skills and Its Relationship to Human Capital - Josephine Diana S Campos; Jofrey R Campos (Research Synergy Foundation, 2023)
This study examines the structural equation model that assessed the relationship of technical skills, conceptual skills, interpersonal skills, and human capital in the food processing industry. The research utilized a model fit, construct reliability, and validity structural equation modeling technique following the reviewed literature. The 204 samples were selected from food processing entrepreneurs in Metro Manila, Philippines. Questionnaires with rating scales were used as research tools, and a random sample procedure was used. A confirmatory factor analysis was used for analyzing model fit, reliability, and validity. A structural model and path analysis were used to examine the link. According to the findings, the model perfectly fits the factual data and indicates an admissible level of validity and reliability. The results positively correlated with Technical Skills, Conceptual Skills, and Interpersonal Skills. Moreover, Human Capital acted as an additional variable to test its relationship with Katz's triplet Managerial Skills, and the findings indicate that Technical Skills, Conceptual Skills, Interpersonal Skills, and Human Capital are correlated. Based on these results, there is a need to augment the technical expertise and conceptual skills pertaining to food processing and offer training that focuses on cultivating interpersonal skills, particularly proficient communication. To improve human capital, it is important to adopt strategies that enhance employee performance. These encompass enhancing proficiency in marketing, financial management, production management, and opportunities for advancement. Future studies should employ qualitative or mixed methods to thoroughly explore the study.